Karakteristik Kadar Total Kolesterol, Trigliserida, dan Kejadian Ulkus Kaki Diabetik pada Pasien Diabetes Melitus Tipe 2 - Aniswati Furqani; Thoha Muhajir Albaar; Nur Upik En Masrika (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Diabetic foot ulcers represent one of the most serious long-term complications associated with type 2 diabetes mellitus, often contributing to increased rates of morbidity and mortality, while significantly impairing patients' quality of life. Among the various underlying causes, peripheral neuropathy and vascular disorders (vasculopathy) are frequently linked to dyslipidemia. This study aimed to examine the characteristics of total cholesterol and triglyceride levels, along with the prevalence of diabetic foot ulcers in patients with type 2 diabetes mellitus. A descriptive retrospective approach was used by analyzing medical record data collected from Dr. H. Chasan Boesoirie General Hospital in Ternate. The findings indicated that the majority of patients with type 2 diabetes were aged 45 years or older (80%) and were predominantly female (60%). In terms of lipid profiles, most patients exhibited normal total cholesterol levels (82.2%) and normal triglyceride levels (51.1%). Despite these normal lipid values, a significant portion of the patients (53.3%) were identified as being at risk of developing diabetic foot ulcers. These results suggest that while dyslipidemia is commonly implicated in the development of diabetic foot complications, normal lipid levels do not necessarily eliminate the risk. The study concludes that the typical profile of type 2 DM patients includes those aged ≥ 45 years, females, and individuals with normal cholesterol and triglyceride levels who are still susceptible to diabetic foot ulcers. This highlights the multifactorial nature of diabetic foot ulcer development and underscores the importance of comprehensive risk assessments beyond lipid profile evaluation alone in diabetic patient care.